Recortes da obra Memorial de Maria Moura: o processo de (re)criação em cena - Pereira, Andrea Cristina Martins (2008)
The expansion over the creation processes studies starting in the 90´s, twentieth century, of literature for the rest of the artistic manifestations, made room for the genetic analysis on new artistic genres, among them those resulting from translations or inter-semiotic recreations. This work is contextualized in this scenery beginning with the process of adaptation of Memorial de Maria Moura, by Rachel de Queiroz, to the written screenplay, and from it to the TV screens, considering the participation of the novel s author in the decision-taking in the final result of the miniseries. Approaching the genetic criticism and the inter-semiotic translation, the work corpus was selected among more than 2000 folios which compose the novel s process documents, the 660 pages of the screenplay and the 10 hours and 45 minutes of the TV work, emphasizing the deepest marks left by the Rachel de Queiroz in the screenplay. The analysis of the three levels of the work creation allows us to evaluate the writer s interference on the TV version of Memorial, in which she likes the most, that is, the character s personality and psychology, Maria Moura.